(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article substantiates the need to use the possibilities of public-private partnership for the “green” development of Ukraine. The purpose of the study is to determine the features of the use of “green” investments in the implementation of public-private partnership projects at all levels of management. In accordance with the goal, the following tasks are set: to find out the structure of “green” investments and their role in the implementation of public-private partnership projects in wartime; explore the types, forms and subjects of public-private partnership in modern conditions; analyze possible risks of international “green” investment in public-private partnership projects in Ukraine during the reconstruction period; identify the existing problems in the use of such forms of public-private partnership in Ukraine as rent and concession for the development of the “green” economy and possible ways to solve them, taking into account the experience of the EU countries. In today’s conditions in Ukraine, local self-government bodies, as well as their associations, began to play an increasing role in the process of building a ‘’green’’ economy. In addition, some democratic countries, which are leaders in the use of “green” investments in the EU, began to help actively Ukraine financially. Analyses of the experience of their use of public-private partnership projects will allow our country to achieve quickly the standards of the Green European Course, since Ukraine has received the status of a candidate for joining the European Union. The expansion of the subjects of public-private partnership requires the creation of the proper conditions for them by the state, which will enable Ukraine to increase significantly “green’’ investments for the reconstruction of the country. Therefore, it is important to study the experience of stimulating the EU countries “green” projects of public-private partnership in various spheres of the economy, use the best of it in Ukraine.